Galdós en el exilio republicano espanol y su recepción hispanoamericana - Domínguez Gutiérrez, M. Carmen (Verba hispanica, 2020)
This work explores the Galdosian reading keys offered by three Spanish republican exiles in Mexico - José Bergamín, Max Aub and Luis Cernuda - as well as the Spanish-American reception - in the figure of Carlos Blanco Aguinaga - of the generation of writers who succeeded Galdós. In the texts of the three exiled intellectuals, the criticisms of writers of the generations following Galdós are taken apart and the writer's centrality in Spanish litera-ture is restored. He is duly recognised as heir to a literary tradition inaugurated by Cervantes, Quevedo and Lope de Vega, precisely for the same reason that Galdós himself highlighted, drawing on his own work, in his acceptance speech on the occasion of his admission the Royal Spanish Academy in 1897, namely his endeavour to novelize the society that surrounded him.
Keywords: Aub, Max; Bergamin, José; Blanco Aguinaga, Carlos; Cernuda, Luis; literarna recepcija; Pérez Galdós, Benito; španski avtorji